MOCAF (MODIFIED CASSAVA FLOUR) TO BOOST INDONESIA'S AGRIBUSINESS ECONOMY - Nina Herlina; Muhammad Zaki Rahman (Proceeding of International Seminar on Agricultural Conservation and Cultural Heritage, 2025)
Indonesia is one of the world's largest cassava producers, yet its economic potential remains underutilized. The development of Modified Cassava Flour (MOCAF) offers a promising opportunity to enhance the value of this crop. MOCAF is a gluten-free flour made from fermented cassava and can serve as a local alternative to wheat flour. This research aims to explore the potential of MOCAF in boosting Indonesia’s agribusiness sector by creating value-added products that can reduce the country’s dependency on imported wheat flour. The study employed a qualitative approach, gathering data through literature reviews, case studies, and expert interviews to assess the economic, technical, and social feasibility of MOCAF. Findings indicate that MOCAF has significant potential to empower rural communities, create local job opportunities, and offer a sustainable solution to food security issues. Additionally, the development of MOCAF could promote food diversification and foster growth in the local food industry. The results highlight that with proper government support and investment in infrastructure, MOCAF production could be scaled up to achieve economic benefits on a national level.